KEBIJAKAN LUARNEGERI AMERIKA SERIKAT TERHADAP KELOMPOK TERORISME AL-QAEDA PADA MASA PEMERINTAHAN BARACK OBAMA - Milia, Jana; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to understand how foreign policy of the United States against terrorist group al-qaeda in the reign of barack obama. in the 21st century, after the cold war, the threat of American countries not only come from the threat of the state, but it can be done by a terrorist group. 9/11 tragedy caused by terrorist group Al-qaeda has brought America into a country at the forefront to fight against the Al-qaeda. after 9/11, the United States changed the focus of foreign policy into a security policy. at that time, America was led by George W. Bush. many controversial policies that under criticism world. such policies to the invasion of Afghanistan and Iraq.in 2009, George Bush was replaced by Barack Obama, who led the United States. Barack Obama is known as a leader in contrast to earlier, it is evident from some of the policies of Bush and Obama are clashing. such as disagreements over Muslim countries.This research theoretically has built with realism perspectives on International Relations and supported by foreign policytheories, and also the concept of non-traditional security. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library.Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that foreign policy of the United States against terrorist group al-qaeda in the reign of barack obamacontinuing the policies the previous president, namely contraterrorism. This is proven from Obama policies such as improving diplomatic relations with Muslim countries, in cooperation with the state of pakistan to fight al-Qaeda, withdrawing troops in Iraq, a military operation neptune spear that had killed the leader of al-Qaeda, plans to close the Guantanamo prison, and Counterinsurgency in Afghanistan.Keywords : Foreign Policy, Terrorism, Al-qaeda, Bush Reign, Barrack Obama